Magnitude of the Digital Placebo Effect and Its Moderators on Generalized Anxiety Symptoms: Systematic Review and Meta-Analysis - Takashi Hosono; Rinka Tsutsumi; Yuki Niwa; Masuo Kondoh (Journal of Medical Internet Research)
AbstractBackground